Pseudoaneurysm of the brachial artery in an infant due to vaccination: a case report - Hai-fei Shi; Shuai Yuan; Ke-jiong Liang; Po Ye; Hu Yang (BMC, 2023)
Abstract Background Pseudoaneurysm is a known complication of penetrating arterial injuries such as catheterization, gunshot wounds, and open fractures. Vaccination is an effective method for preventing multiple, serious, infectious diseases in children. Common adverse reactions related to vaccination include fever, swelling, redness, and pain. Brachial pseudoaneurysm after vaccination has not been previously reported. Case presentation Herein we describe a novel case of brachial pseudoaneurysm after vaccination in a child aged 1 year and 3 months. A pulsatile mass was formed in the medial left arm of the infant 10 days after vaccination at a community hospital and gradually grew larger. Preoperative images depicted an eccentric aneurysm in the brachial artery and a swirling flow pattern in the mass. The pseudoaneurysm was excised, and vein graft interpositioning was successfully performed. There were no short-term or long-term complications during the follow-up period. Conclusions Brachial pseudoaneurysm is a rare complication of vaccination via intramuscular injection. Medical staff should avoid puncture wounds to the brachial artery during vaccination, especially in infants.